Assessing the impact of brand awareness on destination choice among tourists from Gauteng - Seshoka, Lebogang (The IIE, 2026)
This study examines the impact of brand awareness on destination choice among Gauteng-based domestic tourists in South Africa. With tourism growth concentrated in a few key regions like Cape Town and Durban, this research explores how brand awareness can influence travel decisions to lesser-known destinations. The study employed Keller’s Customer-Based Brand Equity model and other relevant frameworks to test the influence of brand recall, brand image, and perceived risk on destination selection. A survey with 271 respondents was conducted, revealing that brand awareness significantly affects destination choice, with 54% of variance in destination affordability attributed to brand-related factors. Brand image emerged as the strongest predictor (β = 0.386), followed by brand awareness (β = 0.243) and brand recall (β = 0.231) in decisions related to cost considerations. Additionally, 60% of the variance in the accessibility of destinations was explained by brand awareness dimensions. The results also indicate that perceived risk, though important, was a weaker predictor (B = -0.074) of destination choice, suggesting tourists prioritise brand recognition over safety concerns. This research provides valuable insights for tourism marketers, recommending strategies to enhance brand visibility for under-visited destinations and foster a more balanced distribution of tourism across South Africa, ultimately contributing to regional economic growth. The study recommends that tourism stakeholders strengthen destination branding through targeted marketing campaigns, improved digital presence, and strategic communication that highlights unique destination attributes. Enhancing brand visibility through social media platforms, partnerships with travel influencers, and integrated marketing strategies may increase awareness and encourage domestic tourists to explore less-promoted destinations. These findings further support Keller’s Customer-Based Brand Equity (CBBE) model by demonstrating how brand awareness dimensions influence tourists’ destination choice behaviour. the study contributes to the growing body of knowledge on destination branding and domestic tourism. Strengthening brand equity for emerging destinations may therefore assist in redistributing tourism demand more evenly across South Africa and contribute to sustainable tourism development and regional economic growth.
Keywords: Digital marketing; Brand identity; Tourism; Social media